2009
DOI: 10.1017/s1368980009005850
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physical activity using accelerometry, an activity diary, the heart rate method and the Indian Migration Study questionnaire in South Indian adults

Abstract: Objective: To validate questionnaire-based physical activity level (PAL) against accelerometry and a 24 h physical activity diary (24 h AD) as reference methods (Protocol 2), after validating these reference methods against the heart rateoxygen consumption (HRVO 2 ) method (Protocol 1). Design: Cross-sectional study. Setting: Two villages in Andhra Pradesh state and Bangalore city, South India. Subjects: Ninety-four participants (fifty males, forty-four females) for Protocol 2; thirteen males for Protocol 1. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 27 publications
1
36
0
1
Order By: Relevance
“…The IMS-PAQ was created by modifying an existing questionnaire and was specifically designed to capture activity patterns and levels across multiple domains relevant to both rural and urban locations in India and across gender as numerous activities are gender specific in India [13,14,16]. The IMS-PAQ was administered by trained interviewers at each study site to gather information on participant's habitual PA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IMS-PAQ was created by modifying an existing questionnaire and was specifically designed to capture activity patterns and levels across multiple domains relevant to both rural and urban locations in India and across gender as numerous activities are gender specific in India [13,14,16]. The IMS-PAQ was administered by trained interviewers at each study site to gather information on participant's habitual PA.…”
Section: Methodsmentioning
confidence: 99%
“…Individual daily activity durations were then summed to generate total daily duration for all reported activities. If this value equated to less than 24 hours, a residual time variable was generated and a standard MET value of 1.4, was applied as in previous studies [14,16]. Individuals over-reporting time spent in daily activities (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies validating physical activity recalls using accelerometry as the gold standard reported stronger average correlation coefficients between energy expenditure estimates (expressed as total energy expenditure, physical activity energy expenditure, average MET per hour, or physical activity MET per week) and accelerometer counts per minute from 24-h recalls than from 7-day recalls (24-h recalls [9,10,41,50,51]: average correlation=.48, range=.23-.82; 7-day recalls [41,51-55]: average correlation=.36, range=−.02-.90). In contrast, average correlations between self-report and accelerometer-based estimates for time spent in sedentary and light activities were greater for 7-day recalls than for 24-h recalls, whereas those for time spent in moderate to vigorous activities agreed across 24-h recalls and 7-day recalls (time spent in sedentary activities among 24-h recalls [10,12]: average correlation=.19, range=−.05-.59; time spent in sedentary activities among 7-day recalls [52,54-57]: average correlation=.37, range=.20-.65; time spent in light activities among 24-h recalls [11,12,58]: average correlation=.18, range=−.16-.45; time spent in light activities among a single 7-day recall [58]: correlation=.37; time spent in moderate to vigorous activities among 24-h recalls [10,11,59,60]: average correlation=.19, range=.05-.26; time spent in moderate to vigorous activities among 7-day recalls [39,55-57,60,61]: average correlation=.26, range=.06-.51).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, average correlations between self-report and accelerometer-based estimates for time spent in sedentary and light activities were greater for 7-day recalls than for 24-h recalls, whereas those for time spent in moderate to vigorous activities agreed across 24-h recalls and 7-day recalls (time spent in sedentary activities among 24-h recalls [10,12]: average correlation=.19, range=−.05-.59; time spent in sedentary activities among 7-day recalls [52,54-57]: average correlation=.37, range=.20-.65; time spent in light activities among 24-h recalls [11,12,58]: average correlation=.18, range=−.16-.45; time spent in light activities among a single 7-day recall [58]: correlation=.37; time spent in moderate to vigorous activities among 24-h recalls [10,11,59,60]: average correlation=.19, range=.05-.26; time spent in moderate to vigorous activities among 7-day recalls [39,55-57,60,61]: average correlation=.26, range=.06-.51). Studies comparing short-term physical activity recalls (24 h to 7 days) with accelerometry tended to report greater estimates of total energy expenditure, light activities, and moderate to vigorous activities (percent difference for total energy expenditure [50,51]: mean=+19%, range=+12%-+31%; for physical activity energy expenditure [49,53]: mean=+87%, range=+80%-+95%; for light activities [11,12,58]: mean=+36%, range=−8%-+107%; for moderate to vigorous activities [11,55,56,59-61]: mean=+260%, range=+29%-+778%). In contrast, there were as many studies overestimating sedentary activities as there were studies underestimating sedentary activities (percent difference for sedentary activities among studies overestimating sedentary activities [11,12,54]: mean=+17%, range=+11%-+27%; among studies underestimating sedentary activities [55-57]: mean=−32%, range=−44% to −13%; among all studies estimating sedentary activities [11,12,54-57]: mean=−4%, range=−44%-+27%).…”
Section: Discussionmentioning
confidence: 99%